2021
DOI: 10.1044/2020_jslhr-20-00492
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Courses in Childhood Dysarthria: Longitudinal Analyses of Auditory-Perceptual Parameters

Abstract: Purpose The aim of this longitudinal study was to describe developmental courses of childhood dysarthria against the background of typical speech motor development by collecting auditory-perceptual data. Method Fourteen children (four girls, 10 boys; 5;1–8;4 [years;months] at Time 1) with neurological conditions (CNC) and 14 typically developing children (CTD) matched for age and gender were assessed at three points in time over an 18-month period. Spee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…A research reported that use of Robertson Dysarthria Profile for the assessment of the client has proven to be effective for speech improvements 20 . Moreover, a survey conducted in UK reports that out of 119 SLTs, 35.3% of them used Robertson Dysarthria Profile for the assessment and treatment of their clients with primary progressive Dysarthria followed by TBI 21 The sensitivity and specificity of the MoCA was found to be 80% and 30%, respectively. The attention sub-scale of the MoCA was also uniquely predictive of rehab success 22 .…”
Section: Discourse Assessmentmentioning
confidence: 99%
“…A research reported that use of Robertson Dysarthria Profile for the assessment of the client has proven to be effective for speech improvements 20 . Moreover, a survey conducted in UK reports that out of 119 SLTs, 35.3% of them used Robertson Dysarthria Profile for the assessment and treatment of their clients with primary progressive Dysarthria followed by TBI 21 The sensitivity and specificity of the MoCA was found to be 80% and 30%, respectively. The attention sub-scale of the MoCA was also uniquely predictive of rehab success 22 .…”
Section: Discourse Assessmentmentioning
confidence: 99%
“…Knowledge about the clinical picture and prognosis of childhood dysarthria is still emerging, with the majority of articles on which current knowledge is based being published over the last ten years (e.g. Allison & Hustad, 2018;Boliek & Fox, 2017;Haas et al, 2021;Hustad et al, 2019;Kuschmann & Lowit, 2021;Levy et al, 2021;Mei et al, 2014;Nordberg et al, 2013;Pennington, Roelant, et al, 2013;Schölderle et al, 2022). And as some of the most common textbooks on dysarthria do not yet consider children as a client group (English: Duffy, 2020;German: Ziegler & Vogel, 2010), it can be challenging for SLPs to acquire knowledge specific to childhood dysarthria.…”
Section: General Challengesmentioning
confidence: 99%
“…Dysarthria usually manifests itself on all functionally relevant speech subsystems, that is, respiration, phonation, articulation and resonance, as well as prosody. As a result, perceptual deviations of speech features can occur to varying degrees in any one or several of these components, causing heterogeneous impairment profiles (Duffy, 2020;Haas et al, 2021;Workinger & Kent, 1991). As part of the dysarthric impairment, children's communication skills are also often impacted, e.g., through reduced intelligibility (e.g., Haas et al, 2022;Hustad et al, 2012;Mei et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Speech samples were collected using the assessment materials of the Bogenhausen Dysarthria Scales for Childhood Dysarthria (BoDyS-KiD; see Haas et al, 2021). BoDyS-KiD is an assessment tool for children with dysarthria that builds upon an approach established for adults, the BoDyS (see Ziegler et al, 2017).…”
Section: Speech Samplesmentioning
confidence: 99%
“…BoDyS-KiD employs a computer game to collect samples of spontaneous speech and a set of repetition sentences (Haas et al, 2021;Schölderle et al, 2020). In particular, a frame story about Astrid Lindgren's "Michel aus Lönneberga," a character who is popular among German children, was used to elicit repetitions of a set of target sentences embedded in the story plot.…”
Section: Speech Samplesmentioning
confidence: 99%